KAJIAN PENGGUNAAN HERBISIDA DAN CARA PENGOLAHAN TANAH PADA PERTUMBUHAN DAN PRODUKSI KEDELAI - Noorhadi Noorhadi; Suwarto Suwarto (Faculty of Agriculture, Universitas Sebelas Maret, 2009)
Title : The Effect of Herbicide and Soil Cultivation to Growth the Soy Bean Yield. This experiment was carried out at Karangasem, Lawiyan, Surakarta. The soil type is Regosol with pH 5.5-6.0. The altitude is about 113 meter. The aims of this experiment were study the effect of soil cultivation and herbicide to growth the soy bean yield. A factorial 4x4 of randomized complete block design was used consisting 16 treatments combinations and three replications as blocks. The result showed that soil cultivation and Agroxone 4 was affected signification as regard to value of intoxication plants at the age of 30 and 45 days, the value of herbicide fought power of weed at the age 20, 30, and 45 days, the soil weed cover at the age of 20, 30, and 45 days, the fresh and dry weight of weed grasses, sedges and broad leaves. Keywords: Glycine max L Merr, Herbicide, Soil Cultivation, soybean